Recombination via transition metals in solar silicon: The significance of hydrogen–metal reactions and lattice sites of metal atoms. Issue 7 (12th June 2017) - Mullins, J.; Leonard, S.; Markevich, V. P.; Hawkins, I. D.; Santos, P.; Coutinho, J.; Marinopoulos, A. G.; Murphy, J. D.; Halsall, M. P.; Peaker, A. R.
Abstract : The move toward lower cost sources of solar silicon has intensified the efforts to investigate the possibilities of passivating or reducing the recombination activity caused by deep states associated with transition metals. This is particularly important for the case of the slow diffusing metals early in the periodic sequence which are not removed by conventional gettering. In this paper, we examine reactions between hydrogen and transition metals and discuss the possibility of such reactions during cell processing. We analyse the case of hydrogenation of iron in p‐type Si and show that FeH can form under non‐equilibrium conditions. We consider the electrical activity of the slow diffusing metals Ti, V, and Mo, how this is affected in the presence of hydrogen, and the stability of TM‐H complexes formed. Finally, we discuss recent experiments which indicate that re‐siting of some transition metals from the interstitial to substitutional site is possible in the presence of excess vacancies, leading to a reduction in recombination activity. Periodic ordering of the 3d, 4d, and 5d transition metals with adjacent columns of the periodic table. The metals with hydrogen complexes which have had their electronic properties reported in the literature or in this paper are highlighted in green.